The Burnout Phenomenon: A Résumé After More Than 15,000 Scientific Publications - Hillert, Andreas; Albrecht, Arnd; Voderholzer, Ulrich (Frontiers in Psychiatry, 2020)
The "burnout" phenomenon, supposedly caused by work related stress, is a challenge for academic psychiatry both conceptually and professionally. Since the first description of burnout in 1974 until today, more than 140 definitions have been suggested. Burnout-symptomatology’s main characteristic, the experience of exhaustion, is unspecific. Different development-models of burnout were proposed, assumed to depict a quasi-natural process.. These could not be confirmed empirically. An expert consensus on the diagnostic criteria and the conceptual location, whether as an independent disorder or as a risk, could not be agreed on. Nevertheless, the phenomenon of burnout in the ICD-11 is considered to be categorized as a work-related disorder. Psychiatric research on the phenomenon burnout, ignores problems of definition resulting from different perspectives: It may meet societal expectations, but does not fulfill scientific criteria, and therefore is not suitable to establish an objective diagnosis and treatment. Parallel detection of ICD / DSM diagnoses from an expert perspective and subjective perturbation models are considered appropriate.